If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2sinx + -4cosx = 0 Reorder the terms: 1 + -4cosx + -2insx = 0 Solving 1 + -4cosx + -2insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -4cosx + -1 + -2insx = 0 + -1 Reorder the terms: 1 + -1 + -4cosx + -2insx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4cosx + -2insx = 0 + -1 -4cosx + -2insx = 0 + -1 Combine like terms: 0 + -1 = -1 -4cosx + -2insx = -1 Add '2insx' to each side of the equation. -4cosx + -2insx + 2insx = -1 + 2insx Combine like terms: -2insx + 2insx = 0 -4cosx + 0 = -1 + 2insx -4cosx = -1 + 2insx Divide each side by '-4osx'. c = 0.25o-1s-1x-1 + -0.5ino-1 Simplifying c = 0.25o-1s-1x-1 + -0.5ino-1 Reorder the terms: c = -0.5ino-1 + 0.25o-1s-1x-1
| 7x-2+3y=40 | | F(-4)=2x+7 | | 5-(8x-7)+18x=-31x-(90+28x)-45 | | 3x+3x+2=4x+2x+3 | | x+2x+4=y | | 25y^2+60y-29=0 | | 2(2-x)=2-(3x-4) | | 315/.021= | | 315/.021 | | 8(7-p)-8=16(16-2) | | In(x+3)-In(x-3)=In(x) | | 3+14s-2=9s+15-2s | | 8=day | | 5x+3-2x=10+8x-3 | | 42-2=3y | | 6[7+3(3*9-7)]= | | 175×5/3 | | 12/3÷2 | | 3(m-5)=2n | | 3cos^2x-2cosx-2=0 | | 3y+x=50 | | 3x+3x+2= | | 3cos^2-2cosx-2=0 | | 20+4t-3=-13+6t | | 6+14t-3=8t+63-4t | | 35=-5/3x | | 9y+14=9y-5 | | 10h+45=15h+20 | | 51-x=31 | | ln(x)+ln(x-4)=12 | | 42/-2= | | 14n+11n= |